ANALISIS DISTRIBUSI PAPARAN SINAR MATAHARI BERDASARKAN ORIENTASI DAN WAKTU MENGGUNAKAN APLIKASI FORMA AUTODESK: STUDI KASUS GEDUNG ARSITEKTUR UNIVERSITAS TADULAKO - Mustakima, Dui Buana; Tamimi, Nadhil; Gamalia, Audita Nurul; Sudyatama, Andi Farid; Munarsi, Munarsi (Universitas Negeri Gorontalo, 2025)
Building orientation is an important aspect of modern architectural design that affects thermal comfort and energy efficiency. This study aims to analyze the influence of various building orientations on solar exposure in buildings located in Palu, Indonesia, which is situated near the equator. The methods used include data collection through physical measurements of buildings, the creation of 3D models, and analysis using the Forma application to measure the duration and intensity of sunlight across different orientations. The research findings indicate that the east-west orientation has the highest potential for optimal sunlight exposure, with 18-22% of the area receiving more than nine hours of sunlight per day, while 57-66% of the other areas only receive 0-1 hour of solar exposure. This study also recommends further research that integrates solar radiation measurements to gain a deeper understanding of the impacts that building orientation can create. It is hoped that these findings will provide significant contributions to planners, developers, and stakeholders, particularly for the city of Palu and areas with similar characteristics.